2000
DOI: 10.1136/bmj.320.7244.1246
|View full text |Cite|
|
Sign up to set email alerts
|

Patients' unvoiced agendas in general practice consultations: qualitative study

Abstract: Objective To investigate patients' agendas before consultation and to assess which aspects of agendas are voiced in the consultation and the effects of unvoiced agendas on outcomes. Design Qualitative study. Setting 20 general practices in south east England and the West Midlands. Participants 35 patients consulting 20 general practitioners in appointment and emergency surgeries. Results Patients' agendas are complex and multifarious. Only four of 35 patients voiced all their agendas in consultation. Agenda it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
316
0
11

Year Published

2001
2001
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 471 publications
(345 citation statements)
references
References 10 publications
13
316
0
11
Order By: Relevance
“…This suggests the potential for mismatch between GP and patient consultation agendas, which may act as an important obstacle to therapeutic alliance. Consultation agendas frequently go unspoken, leading to misunderstandings and frustration 25 . Previous studies have found similar differences in patients' and doctors' goals, with patients primarily seeking support, whilst physicians primary goal is symptom alleviation.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests the potential for mismatch between GP and patient consultation agendas, which may act as an important obstacle to therapeutic alliance. Consultation agendas frequently go unspoken, leading to misunderstandings and frustration 25 . Previous studies have found similar differences in patients' and doctors' goals, with patients primarily seeking support, whilst physicians primary goal is symptom alleviation.…”
Section: Discussionmentioning
confidence: 99%
“…Probably, this is also the case in selflimiting illnesses; mutual misunderstanding and ignorance or disagreement about views on health and illness may negatively influence patient-doctor relationship, patient compliance regarding advice and treatment, and patient satisfaction [21,31,32]. Therefore, exploration of these dimensions of patient's views is needed for optimal patient education and treatment of patients with self-limiting illnesses as respiratory tract symptoms as well as chronic diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that GPs rarely make patients' agendas (including their expectations) explicit in the consultation 4 and that they probably overestimate the patient's expectations of a prescription. 5,6 Exploring the patient's expectations and beliefs is therefore key to ensuring that prescribing is necessary and likely to bring benefit.…”
Section: Factors That Affect Concordancementioning
confidence: 99%
“…During the consultation, patients should be asked questions on their views and beliefs about their illness and treatment, and these must be explored fully before a decision on treatment is reached jointly between the healthcare professional and the patient. 10,11 • After a medicine has been prescribed, patients should have access to ongoing support so that any problems or questions that may arise can be addressed. Healthcare professionals should use all opportunities to talk with patients about their treatment and resolve any practical difficulties; medicines should also be reviewed regularly -with patients.…”
Section: How To Achieve Concordancementioning
confidence: 99%